Experimental analysis and detailed micro-modeling of masonry walls subjected to in-plane shear. (January 2019) - Drougkas, Anastasios; Roca, Pere; Molins, Climent
Highlights: A detailed experimental campaign is presented dealing with masonry walls subjected to shear. The masonry walls are modeled using detailed micro-modeling techniques. Good agreement is found between the experimental and the numerical results. The importance of the compressive strength of masonry is highlighted.